The Maya Art of Speaking Writing : Remediating Indigenous Orality in the Digital Age - Miller, Tiffany D. Creegan, 1983- (Book collections on Project MUSE., 2022)
"Challenging the distinctions between "old" and "new" media and narratives about the deprecation of orality in favor of inscribed forms, The Maya Art of Speaking Writing draws from Maya concepts of tz'ib' (recorded knowledge) and tzij, choloj, and ch'owen (orality) to look at expressive work across media and languages"--